Wave-based and Geometric Representations of Sound Fields - Annibale, Paolo; Antonacci, Fabio; Canclini, Antonio; Rabenstein, Rudolf; Sarti, Augusto (9. ITG Fachtagung Sprachkommunikation, 2010)
The two main approaches for the description of sound fields are methods derived from solutions of the wave equation and geometric methods based on analogies to ray optics. Their mathematical representations are reviewed and it is shown that representations by projective geometry and descriptions by Fourier acoustics lead to similar parametric representations of sound field